Case of giant cell tumour of proximal tibia treated with intra-lesion curettage with adjuvant therapy and reconstruction with the sandwich technique fixation - Moaiyadi, Aliasger H.; Wankhede, Aniket K.; Badole, Chandrashekar M.; Patond, Kisan R. (International Journal of Research in Orthopaedics, 2022)
Giant cell tumour (GCT) of bone is a benign but locally aggressive tumour with the potential of malignant transformation that mostly involves the meta-epiphyseal region of long bones. A 34-year-old female was presented to our institute with progressive pain and swelling in her right knee and was radiologically and histologically found to have a GCT of proximal tibia. She was treated with extended curettage with power burr, intra-lesion phenol application and internal fixation using the sandwich technique. No recurrence was found and the procedure led to a good functional outcome. A GCT of proximal tibia treated with joint preserving surgery with extended curettage and the sandwich technique fixation gives optimal results leading to a good functional outcome.